The Materiality of Water - Mark Harris (Aesthetic Investigations, 2015)
Recordings of water have been an important focus for composers and sound and video artists. Works by Wendy Carlos (Sonic Seasonings), Jane Grant (Fathom), Annea Lockwood (World Rhythms, A Sound Map of the Danube), Hildegard Westerkamp (Talking Rain), Frances White (Walk Through Resonant Landscape), Jana Winderen (Surface Runoff, Evaporation, Aquaculture), and video works by Véréna Paravel (Leviathan), Pipilotti Rist (Pickelporno, Supersubjektiv, Rain Woman) feature the sounds of water as prominent sonic components. Whether similar qualitatively, water sounds have also preoccupied male composers from John Cage to Chris Watson. It’s likely that there are acoustic features developed in these compositions that constitute a kind of listening that is different from what is experienced through other compositional approaches. This retrieval of frequently unmanipulated natural sounds accommodates what is offered up by one’s environment and implies an ecology of matter distinct from other experimental sound practices. Luce Irigaray’s concept of liquidity as a condition of movement and equivocation in ‘The Mechanics of Fluids’ has been cited to articulate a feminist dimension to Rist’s videos, yet what other kinds of materialities are delineated by artists having recourse to an acoustics of fluids? If characterizing these as gendered soundscapes over-essentialises the work and restricts women’s participation in sound production, what draws these respective composers to the properties of water’s materiality as these are accessed by its sound?